Government Effectiveness Towards Community Organizers From The View of Governance - Akram, Khairil; Sumarna, M. Ibnu; Zulfikar, Muh. Reza (Manunggal Halim Jaya, 2025)
This study was conducted due to the demands of the community for fast, precise, and efficient implementation of public services. The government innovates by implementing an e-government system, or electronic-based public services. This research uses a qualitative approach and concentrates on the effectiveness of state administrative law on online public services. This research shows that the effects of the e-government program are close to efficient, as shown by the number of people who have been able to use e-government services. However, not all Indonesians can use these services, as shown by the large number of people in areas where people are still poor and technology illiterate, and there are still many areas that do not have e-government services.